Estimation of Postmorterm Interval by Using Myoglobin Concentration in Blood, Liver And Parotid Glands of Albino Rats - Nasir, Rabia; Ibrahim, Sadaat; Abbas, Aatiqa; Malik, Arif Rasheed; Kashif, Noureen; Munawwar Awan, Mohsin (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the postmortem interval (PMI) by estimating myoglobin concentration in blood, liver and parotid gland of albino rats and to compare the postmortem level of myoglobin among blood, liver and parotid gland.Study Design: Quasi-Experimental study.Place and Duration of Study: Department of Forensic Medicine and Toxicology King Edward Medical University, Lahore in collaboration with the University of Veterinary and Animal Sciences, Lahore from 20 June 2021 to 19 June 2022.Methodology: A total of 72 rats were killed by cervical dislocation and postmortem myoglobin levels were checked in blood, liver and parotid gland at 8 different postmortem intervals (9 rats in each interval) to check its significance in relation to postmortem time.Results: There was a significant correlation between myoglobin concentration in blood, liver and parotid gland with Postmortem Interval with p value of < 0.001. The analysis indicated that the combination of blood, liver, and parotid myoglobin concentrations yielded the highest predictive accuracy (r = 0.982). The next best model included liver and parotid myoglobin concentrations (r = 0.980), while the model based solely on liver myoglobin concentration had the lowest predictive accuracy (r = 0.946).Conclusion: The myoglobin concentration in glandular tissues is a helpful parameter to determine PMI. As the postmortem interval increases the myoglobin concentration in the blood, liver and parotid gland also increases.